Feasibility of Implementing "Low-Crop Planting" in Order to Restore Jazmoryan wetland; Case Study: Jiroft County - Hamed Eskandari Damaneh; Hossein Noroozi; Hassan Khosravi; Hamed Rafiee; Emran Taheri Rykande (Rāhburdhā-yi tusi̒ah-i rūstāyī, 2015)
Jazmoryan Wetland is one of the most sensitive ecosystems in the South East of the country which is declining due to dam construction in upstream as well as deficiency of environmental water supply. The wetland seem to dry out due to its geographical location and construction of Bampour Diversion Dam and Jiroft Reservoir Dam on major rivers flowing to this wetland. One of the solutions proposed by some researchers to restore the aquatic environments is to fallow some parts of irrigated lands fed by water behind the dams and release these resources. Hence, the present study was aimed to investigate the feasibility of implementing low-crop planting plan to restore Jazmoryan wetland. The study was run by using data from 212 questionnaires in 2014. In order to analyze the factors affecting the participation of farmers in the project, a two-stage Heckman method consisting of two patterns of probit and linear regression was used. The results of probit pattern showed that variables of acreage, education, occupation, number of household members and income of farmers had a significant effects on their willingness to participate in the restoration of Jazmoryan wetland. However, according to the results of linear regression pattern, variables of acreage, age, education, marriage status, number of household members and income had a significant effects on the willingness of farmers to participate in the restoration of Jazmoryan wetland. According to the results, 61% of farmers were not willing to participate in the proposed plan. It is suggested that if the government is willing to implement low-crop planting project, the percentage of participation in the plan will be increased by developing appropriate lateral plans and presenting solutions which are accepted by the farmers.